Evaluation of the Water Quality Status of the Kedunguling River Using the Pollution Index Method in Durung Banjar Village, Sidoarjo - Ahza Refkyan Dhafa; Listin Fitrianah (CV Edujavare Publishing, 2026)
The Kedunguling River is a water body that functions as a drainage channel and supports community activities in Durung Banjar Village, Sidoarjo Regency. Increased domestic and industrial activities around the river have the potential to reduce water quality through the entry of organic and inorganic pollutants. This study aims to analyze the water quality of the Kedunguling River based on the parameters of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Lead (Pb), Chromium (Cr), pH, and Total Dissolved Solids (TDS), and determine the water quality status using the Pollution Index (IP) method. The study was conducted with a quantitative descriptive approach using the grab sampling method at five observation points representing conditions before and after the pollution source. Sampling was carried out twice with a two-week interval. The test results showed that the BOD value ranged from 3.69–7.90 mg/L, COD 12.30–26.40 mg/L, Pb <0.0195 mg/L, Cr <0.0193 mg/L, pH 7.3–7.7, and TDS 288–300 mg/L. Most parameters still meet the water quality standards for class III according to Government Regulation Number 22 of 2021. The results of the Pollution Index calculation showed that all points in the 1st week had a status that met the quality standards with an IP value of 0.56 and in the 3rd week with an IP value of 0.73. This condition indicates an increase in the load of organic pollutants at certain locations which is suspected to originate from domestic activities and environmental runoff around the river.